Foreign elements in the english language vocabulary / Kamisah Ariffin - Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2001)
With the United Kingdom and the United States of America as the giants of the world economic power, the importance of English, which is the first language of these countries, is naturally and undeniably great. Claimed as having more than 500,000 in word power, no other languages in the world has been its equal though some like French and Spanish have attempted to compete against it. What makes English acceptable worldwide is its vocabulary. The mixed character of its vocabulary through adoption, assimilation and incorporation from other languages enables it to be 'shared' by the speakers of the languages it borrows, and thus, makes it some kind of familiar to those speakers.